Tindak Tutur Direktif Calon Guru dengan Siswa Kelas VIII pada Pelajaran Bahasa Indonesia - Dhiba Riswinda Fajar; Nur Aini Puspitasari (Universitas Indraprasta PGRI, 2023)
Pre-service teacher is the main subject for students in the teaching and learning process. Because of this matter, they are required to provide Indonesian language teaching with simple delivery, but still in the directed, good, and correct speech in order to avoid misunderstanding during interactions. Successful learning can be identified by looking at the students' development on the subject being taught by the pre-service teacher which can make students engaged to the learning process. This research aimed to find out the directive speech acts utilized by the pre-service teacher including the sub-category that are Command, Beseech, Ask to, Warn, Advise to, Beg, and Recommend. The method used in this research was qualitative descriptive. The data were collected through observation and recording. Alan Cruse's theory of directive speech acts was used as the research instrument. The results of this research showed that Command and Ask to were the speech acts that were mostly used by the pre-service teacher. In addition, a pre-service teacher also used the speech acts of Beseech, Warn, Advise to, Beg, and Recommend during the teaching and learning process.Keywords: Pre-service teacher; speech acts; students.